Clinical features and genetic analysis of 15 Chinese children with dent disease - Qian Li; Zhenle Yang; Ruixian Zang; Suwen Liu; Lichun Yu; Jing Wang; Cong Wang; Xiaoyuan Wang; Shuzhen Sun (Renal Failure)
Objective  The clinical characteristics, genetic mutation spectrum, treatment strategies and prognoses of 15 children with Dent disease were retrospectively analyzed to improve pediatricians’ awareness of and attention to this disease.Methods  We analyzed the clinical and laboratory data of 15 Chinese children with Dent disease who were diagnosed and treated at our hospital between January 2017 and May 2023 and evaluated the expression of the CLCN5 and OCRL1 genes.Results  All 15 patients were male and complained of proteinuria, and the incidence of low-molecular-weight proteinuria (LMWP) was 100.0% in both Dent disease 1 (DD1) and Dent disease 2 (DD2) patients. The incidence of hypercalciuria was 58.3% (7/12) and 66.7% (2/3) in DD1 and DD2 patients, respectively. Nephrocalcinosis and nephrolithiasis were found in 16.7% (2/12) and 8.3% (1/12) of DD1 patients, respectively. Renal biopsy revealed focal segmental glomerulosclerosis (FSGS) in 1 patient, minimal change lesion in 5 patients, and small focal acute tubular injury in 1 patient. A total of 11 mutations in the CLCN5 gene were detected, including 3 missense mutations (25.0%, c.1756C > T, c.1166T > G, and c.1618G > A), 5 frameshift mutations (41.7%, c.407delT, c.1702_c.1703insC, c.137delC, c.665_666delGGinsC, and c.2200delG), and 3 nonsense mutations (25.0%, c.776G > A, c.1609C > T, and c.1152G > A). There was no significant difference in age or clinical phenotype among patients with different mutation types (p > 0.05). All three mutations in the OCRL1 gene were missense mutations (c.1477C > T, c.952C > T, and c.198A > G).Conclusion  Pediatric Dent disease is often misdiagnosed. Protein electrophoresis and genetic testing can help to provide an early and correct diagnosis.